Inflation Anchoring and Growth : Evidence from Sectoral Data - Choi, Sangyup; Furceri, Davide; Loungani, Prakash (Washington, D.C. : International Monetary Fund, 2018)
Central bankers often assert that low inflation and anchoring of inflation expectations are good for economic growth (Bernanke 2007, Plosser 2007). We test this claim using panel data on sectoral growth for 22 manufacturing industries for 36 advanced and emerging market economies over the period 1990-2014. Inflation anchoring in each country is measured as the response of inflation expectations to inflation surprises (Levin and others, 2004). We find that credit constrained industries-those characterized by high external financial dependence and R and D intensity and low asset tangibility-tend to grow faster in countries with well-anchored inflation expectations. The results are robust to controlling for the interaction between these characteristics and a broad set of macroeconomic variables over the sample period, such as financial development, inflation, the size of government, overall economic growth, monetary policy counter-cyclicality and the level of inflation. Importantly, the results suggest that it is inflation anchoring and not the level of inflation per se that has a significant effect on average industry growth. Finally, the results are robust to IV techniques, using as instruments indicators of monetary policy transparency and independence.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet